Indigo: A Natural Molecular Passivator for Efficient Perovskite Solar Cells. Issue 22 (22nd April 2022) - Guo, Junjun; Sun, Jianguo; Hu, Long; Fang, Shiwen; Ling, Xufeng; Zhang, Xuliang; Wang, Yao; Huang, Hehe; Han, Chenxu; Cazorla, Claudio; Yang, Yingguo; Chu, Dewei; et al.
Abstract: Organic–inorganic hybrid lead halide perovskite solar cells have made unprecedented progress in improving photovoltaic efficiency during the past decade, while still facing critical stability challenges. Herein, the natural organic dye Indigo is explored for the first time to be an efficient molecular passivator that assists in the preparation of high‐quality hybrid perovskite film with reduced defects and enhanced stability. The Indigo molecule with both carbonyl and amino groups can provide bifunctional chemical passivation for defects. In‐depth theoretical and experimental studies show that the Indigo molecules firmly binds to the perovskite surfaces, enhancing the crystallization of perovskite films with improved morphology. Consequently, the Indigo‐passivated perovskite film exhibits increased grain size with better uniformity, reduced grain boundaries, lowered defect density, and retarded ion migration, boosting the device efficiency up to 23.22%, and ≈21% for large‐area device (1 cm 2 ). Furthermore, the Indigo passivation can enhance device stability in terms of both humidity and thermal stress. These results provide not only new insights into the multipassivation role of natural organic dyes but also a simple and low‐cost strategy to prepare high‐quality hybrid perovskite films for optoelectronic applications based on Indigo derivatives. Abstract : Natural organic dye Indigo is for the first time demonstrated as a low‐cost and highly efficient molecular passivator for high performance perovskite solar cells and the Indigo passivation boosts power conversion efficiency of device up to 23.22% as well as enhances device stability both in terms of humidity and thermal stress.